Clinical Considerations Regarding the Use of Obesity Pharmacotherapy in Adolescents with Obesity. Issue 2 (24th January 2019) - Srivastava, Gitanjali; Fox, Claudia K.; Kelly, Aaron S.; Jastreboff, Ania M.; Browne, Allen F.; Browne, Nancy T.; Pratt, Janey S. A.; Bolling, Christopher; Michalsky, Marc P.; Cook, Stephen; Lenders, Carine M.; Apovian, Caroline M.
Abstract : A growing number of youth suffer from obesity and in particular severe obesity for which intensive lifestyle intervention does not adequately reduce excess adiposity. A treatment gap exists wherein effective treatment options for an adolescent with severe obesity include intensive lifestyle modification or metabolic and bariatric surgery while the application of obesity pharmacotherapy remains largely underutilized. These youth often present with numerous obesity‐related comorbid diseases, including hypertension, dyslipidemia, prediabetes/type 2 diabetes, obstructive sleep apnea, nonalcoholic fatty liver disease, musculoskeletal problems, and psychosocial issues such as depression, anxiety, and social stigmatization. Current pediatric obesity treatment algorithms for pediatric primary care providers focus primarily on intensive lifestyle intervention with escalation of treatment intensity through four stages of intervention. Although a recent surge in the number of Food and Drug Administration‐approved medications for obesity treatment has emerged in adults, pharmacotherapy options for youth remain limited. Recognizing treatment and knowledge gaps related to pharmacological agents and the urgent need for more effective treatment strategies in this population, discussed here are the efficacy, safety, and clinical application of obesity pharmacotherapy in youth with obesity based on current literature. Legal ramifications, informed consent regulations, and appropriate off‐label use of these medications in pediatrics are included, focusing on prescribing practices and prescriber limits.